Clinical Characteristics, Metabolic Parameters, and Risk Factors for Suicide Attempts Vary with Untreated Major Depressive Disorder Duration - Tong, P.; Shi, Y. H.; Yang, Y.; Dong, L. P.; Wu, L. L.; Sun, T. T.; Lu, W.; Zhang, X. Y. (Depression and Anxiety, 2023)
Suicidal attempts (SAs) are common in major depressive disorder (MDD). However, only few studies have so far assessed how risk factors for SAs in patients with MDD might be related to the duration of untreated illness (DUI). We interviewed 1,718 drug-naive outpatients with MDD with first-episode SAs and divided them into groups that had and had not attempted suicide. DUI was used as an additional grouping criterion. The patients (20.14%; 346/1718) who had a history of SAs were older and had a longer DUI; lower educational level (middle school-educated only); more psychotic symptoms; higher scores on depression and anxiety scales; and higher BP, plasma BG, TC, and LDL-C levels, but lower HDL-C concentrations. Anxiety symptoms, high education level, and being unmarried were risk factors for SA in patients with MDD with DUIs of <3 months; anxiety symptoms, low BMI, high plasma TC, and low plasma HDL-C were risk factors for SA in the group with DUIs between 3 and 8 months; age, anxiety symptoms, and higher systolic blood pressure were risk factors for those with DUIs>8 months. This study was a single-center cross-sectional survey, and its limitations include a lack of outside validation. Patients with MDD with and without a SA history have different clinical characteristics and metabolic parameters, and risk factors for suicide vary across DUI stages. Anxiety was a general risk factor, suggesting that clinicians should strengthen their assessment of SA risk in patients with MDD during diagnosis and treatment.